2008
DOI: 10.1108/ijsms-10-01-2008-b006
|View full text |Cite
|
Sign up to set email alerts
|

The internationalisation of a sports team brand: the case of European soccer teams

Abstract: Building on previous research, the academic contribution of this research lies mainly in the conceptualisation of the internationalisation of a sports team brand as well as with an explanation of how a sports team can position itself as an international global brand. In this paper, we articulate a model on the internationalisation of a sports team brand. After a thorough analysis of the literature, we propose four strategies, which are relevant to the sports arena: i) Brand Reputation (think local, act global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…This symbolic approach to branding reinforces the concept of developing customer-based brand equity (Keller, 1993) which in this study occurs when fans and organisations are familiar with the brand and hold favourable, strong and unique associations. The more exclusivity in the material offered by players will help to develop knowledge and a shared identity to drive positive sentiment and brand affinity (Richelieu et al, 2008) complimenting the work by Armstrong et al (2014) who found that teams were able to nurture a unique identity through their creative and human approach to social networking.…”
Section: Discussionmentioning
confidence: 86%
“…This symbolic approach to branding reinforces the concept of developing customer-based brand equity (Keller, 1993) which in this study occurs when fans and organisations are familiar with the brand and hold favourable, strong and unique associations. The more exclusivity in the material offered by players will help to develop knowledge and a shared identity to drive positive sentiment and brand affinity (Richelieu et al, 2008) complimenting the work by Armstrong et al (2014) who found that teams were able to nurture a unique identity through their creative and human approach to social networking.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, their success is based on their ability to enhance the perception and the recognition of symbols associated with them.'' Branding is recognized as a strategic leverage for sport organizations, both nationally and internationally (Chanavat & Bodet, 2009;Richelieu, Lopez, & Desbordes, 2008) and is one of its major assets (Bauer, Sauer, & Schmitt, 2005). Its strength is one of the main drivers of fans' commitment and purchasing merchandize which allows them to self-identify with their club (Richelieu & Pons, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, to create value for a brand, consumers (i.e., fans) must develop positive and unique brand associations toward that brand; however, they first need to become familiar with it 13,14 . Previous studies have suggested the roles of different sources, such as the media 15 , oral communication 16 , impression management 17 , social agents 18 , and team and/or sport 19 , on brand and athletes, which help familiarize fans with them. Consistent with this perspective, Montoya 20 explained that developing an athlete brand requires fans' awareness about the athlete and an understanding of how he/she is different from other athletes.…”
Section: Introductionmentioning
confidence: 99%